Paradigama Perubahan Pendidikan Keagamaan - Aden Wijdan SZ (Universitas Islam Indonesia, 2005)
The religious education paradigm declares that tends to ritual formal textualist. The basic assumption of the paradigm states that holy scripture can overcome most of problem that human facing wherever and whenever. Besides, it is so difficult to change society and the process of education itself. To solve problems above mentioned, the religious education needs a new and dynamic perspective, till it can change in accordance with expectation. According to the writer of this article, it is clear that paradigm of religious education that can overcome most of problem of education nowadays is substantivistic, inclusivistic, and that of pluralistic.